Childhood traumatic experiences and dimensional models of personality disorder in DSM-5 and ICD-11: opportunities and challenges - Back, Sarah Naomi; Flechsenhar, Aleya; Bertsch, Katja; Zettl, Max (Current psychiatry reports, 2021)
Childhood trauma is an important risk factor for the development of personality disorders (PDs), yet most research has been devoted to categorical models of personality pathology. Considering the introduction of a dimensional PD model with ICD-11, we review current findings related to various forms of childhood trauma, and PDs, operationalized in the form of personality functioning and maladaptive traits. We focus on the magnitude of associations and examine specific relationships between emotional and physical trauma with areas of personality functioning and single traits.
Gesehen am 25.10.2021